2017
DOI: 10.1097/wnr.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Altered electroencephalogram complexity in autistic children shown by the multiscale entropy approach

Abstract: Autism spectrum disorder (ASD) is a severe neurodevelopment disorder. This study tests the hypothesis that children with ASD show atypical intrinsic complexity of brain activity. Electroencephalogram data were collected from boys with ASD and matching normal typically developing children while performing an observation and an imitation task. The multiscale entropy was estimated within the 0.5–30 Hz frequency band over 30 time scales using a coarse-grained procedure. A decreased electroencephalogram complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…Decreased EEG complexity in individuals with ASD was also found during observation and imitation tasks over central, parietal, occipital, and right temporal areas. These areas were compatible with the areas activated during imitation tasks in fMRI studies and may indicating a deficit in the "mirror neuron system" in ASD [16,56]. Treatments of ASD-related symptoms may also affect EEG complexity.…”
Section: Autism Spectrum Disordersupporting
confidence: 65%
“…Decreased EEG complexity in individuals with ASD was also found during observation and imitation tasks over central, parietal, occipital, and right temporal areas. These areas were compatible with the areas activated during imitation tasks in fMRI studies and may indicating a deficit in the "mirror neuron system" in ASD [16,56]. Treatments of ASD-related symptoms may also affect EEG complexity.…”
Section: Autism Spectrum Disordersupporting
confidence: 65%
“…Multi-domain features are captured to highlight the characteristics of EEG signals, e.g., information entropy, timefrequency analysis, and synchronization analysis. Specifically, information entropy features are first obtained by measuring the complexity of the original EEG signal individually along each channel, e.g., approximate entropy (ApprEn, Meedeniya et al, 2019), sample entropy (SampEn, Liu et al, 2017), and permutation entropy (PermEn, Kang et al, 2019). Then, the original EEG is processed by short-time Fourier transforms (STFT) to capture the time-frequency representation, e.g., entropy feature.…”
Section: Feature Extractionmentioning
confidence: 99%
“…The primary disruption is likely to be in these systems themselves, and the measured action kinematics a manifestation of those neural disruptions. Therefore, kinematic studies that address fundamental motor control theory, such as feed-forward and feed-back systems in motor control (Nazarali et al, 2009), prospective motor control such as shown for infant movement (Delafield-Butt et al, 2018;Gottwald et al, 2016;Lee, 2009), predictive coding in motor systems (Gonzalez-Gadea et al, 2015;Van de Cruys et al, 2014) or entropy analyses (Liu et al, 2017) will begin to afford insight into disruptions of those neural systems in autism. The advantage of the methodology we employ here is rapid, nonintrusive collection of precise laboratory-grade kinematic data within an ecologically valid, fun, and attractive serious game format.…”
Section: Discussionmentioning
confidence: 99%